Multiple Daily Rounds of Theta-Burst Stimulation for Tinnitus: Preliminary Results - Seok-Min Hong; Sung-Kyun Kim; Moo-Young Seo; Suk-Yun Kang (Medicina, 2021)
Background and Objectives: Tinnitus is a condition that negatively affects the quality of life and is difficult to treat. Theta burst stimulation (TBS), a new method of repetitive transcranial magnetic stimulation (rTMS), is a promising treatment approach because it shows stronger and more prolonged effects in a shorter time of stimulation than other rTMS protocols. However, the therapeutic effect of TBS for tinnitus was inconsistent. We hypothesized that more stimulation would be more effective. Therefore, this study aimed to explore the safety and effectiveness of multiple daily rounds of TBS over five consecutive days. Materials and Methods: The continuous TBS (cTBS) protocol is 300 pulses/day, but we applied 8 sessions of 300 pulses in a day (total 2400 pulses/day). A total of 15 patients with tinnitus were randomly assigned to treatment and sham groups. Outcome measurements were taken three times: before and after 5-day of stimulation; at a 1–3 month follow-up visit. Outcome measurements were the degree of annoyance due to ear fullness, duration of tinnitus, visual analog scales of tinnitus for annoyance, Tinnitus Handicap Inventory, pitch, loudness, minimum masking level, and residual inhibition. Results: Five-day cTBS was completed without adverse events. We did not find any significant therapeutic effect in the treatment group, but we needed to be cautious to interpret our result due to the small sample size. Conclusions: In conclusion, multiple rounds of cTBS in a day may be safe. Further research is needed in a larger sample size to determine the effectiveness and confirm the safety.